Strategia i polityka gospodarcza kraju w latach dziewięćdziesiątych w zakresie infrastruktury wsi i rolnictwa - Wilczyńska, Kamila (Wydział Prawa i Administracji UAM, 1991)
The change of the economic system in Poland, i.e. the transformation of the centrally managed economy into market economy brings about a series of consequences in the economic strategy and policy towards the infrastructure of villages and agriculture. There appears a set of problems connected with the future forms of ownership of infrastructural objects, with the ways of financing investment in this sphere and with the exploitation of such objects. There appears a problem of the scope of self-financing of the infrastructure, and, in effect, the problem of burdening the population and farms with such costs. Besides, it should always be remembered that while such investments require a high capital input, they are a necessary condition for the development of food economy of the country. In such a situation shifting the infrastructural outlay to the local self-government makes it necessary to depart from gigantic projects which require high capital outlays and are very expensive in exploitation. A highly diversified level of agricultural infrastructure throughout the country stimulates discussions pointing to the need of eliminating the differences. It could be achieved through investing in the least developed areas. The economic strategy and policy which would be aimed only at showing down the decapitalization of infrastructure in the western part of the country would be in disagreement with the principle of optimum allocation of resources. The article presents many fundamental dilemmnas and postulated connected with the analysed segment of the economic policy of the country and the region. The considerations and documentation lead to the conclusion that it is necessary to implement the interventionist policy of the State towards agriculture in the form of modernization and development of the infrastructure of villages and agriculture.
Economic strategy and policy in Poland towards the infrastructure of villages and agriculture in the 1990s